AB0571 High Dose Intravenous Methylprednisolone Induces RAPID Improvement in Severe Ocular Inflammation. Multicenter Study of 104 Cases. (10th June 2014) - Beltrán-Catalán, E.; Calvo-Río, V.; Blanco-Alonso, R.; Ortego Centeno, N.; García Serrano, J.L.; Martinez-Costa Pérez, L.; Fonollosa Calduch, A.; Hernandez Garfella, M.; Valls, E.; Francisco Hernández, F.; Reyes, M.A.; Torre, I.; et al.
Abstract : Background: Intense ocular inflammation can cause an early and irreversible structural and functional damage. Objectives: Treatment with high-dose intravenous methylprednisolone (IVMP) can induce a rapid improvement in multiple inflammatory conditions including uveitis. Methods: A multicenter study of 104 patients (169 eyes) with severe ocular inflammation treated with IVMP attended in uveitis units of 11 hospitals. The most frequent underlying syndromes were: idiopathic uveitis (n=21), Vogt-Koyanagi-Harada (n=26), Behçet (n=19), spondyloarthritis (n=4), Sjögren syndrome (n=2), psoriatic arthritis (n=2) and multiple Sclerosis (n=2). The patients were evaluated at baseline and on days 2-5, 7, 15 and 30 after treatment with IVMP. Results: 104 patients (59 women/45 men) were studied with a mean age of 42.27±14.42 years (range 8-76 years) receiving doses of IVMP, which ranged from 0.25 to 1 gram per day for 2-5 consecutive days. They all had active and severe intraocular inflammation at baseline. The inflammatory ocular patterns were: panuveitis (n=61), posterior uveitis (n=35), anterior uveitis (n=3), scleritis (n=3) and intermediate uveitis (n=2). Bilateral ocular involvement was observed in 65 patients (62.5%). After IVMP treatment, the inflammation of the anterior chamber, the vitritis and visual acuity experienced rapid and statistically significant improvement from the second day. However, the improvement of retinal vasculitis, choroiditis/chorio-retinitis and macular edema was more slowly achieved, gaining statistical significance from the first week. Optical coherence tomography (OCT) showed a macular thickening (>250μ) in 90 eyes at baseline, with normalization in 30% of affected eyes at day 15 and in 50% of affected eyes at day 30 (p<0.05). IVMP therapy was well tolerated and no notable side effects were reported. Conclusions: Our study suggests that IVMP is an effective and safe remission induction therapy in severe ocular inflammation. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4735